The Retrospective Analysis of Posterior Short-Segment Pedicle Instrumentation without Fusion for Thoracolumbar Burst Fracture with Neurological Deficit. (2nd March 2014) - Deng, Zhouming; Zou, Hui; Cai, Lin; Ping, Ansong; Wang, Yongzhi; Ai, Qiyong
Abstract : This study aims to investigate the efficacy of posterior short-segment pedicle instrumentation without fusion in curing thoracolumbar burst fracture. All of the 53 patients were treated with short-segment pedicle instrumentation and laminectomy without fusion, and the restoration of retropulsed bone fragments was conducted by a novel custom-designed repositor (RRBF). The mean operation time and blood loss during surgery were analyzed; the radiological index and neurological status were compared before and after the operation. The mean operation time was 93 min (range: 62–110 min) and the mean intraoperative blood loss was 452 mL in all cases. The average canal encroachment was 50.04% and 10.92% prior to the surgery and at last followup, respectively (P < 0.01 ). The preoperative kyphotic angle was 17.2 degree (±6.87 degrees), whereas it decreased to 8.42 degree (±4.99 degrees) at last followup (P < 0.01 ). Besides, the mean vertebral body height increased from 40.15% (±9.40%) before surgery to 72.34% (±12.32%) at last followup (P < 0.01 ). 45 patients showed 1-2 grades improvement in Frankel's scale at last followup. This technique allows for satisfactory canal clearance and restoration of vertebral body height and kyphotic angle, and it may promote the recovery of neurological function. However, further research is still necessary to confirm the efficacy of this treatment.